PENGARUH EFIKASI DIRI, TEMAN SEBAYA, DAN INTEGRITAS SISWA TERHADAP KECURANGAN AKADEMIK - Aurel, Dinda Natasya; Fauzi, Achmad; Susanti, Santi (Transpublika Publisher, 2023)
This study aims to determine the effect of self-efficacy, peers, and student integrity on academic cheating. The study uses quantitative methods with survey methods, including validity tests, reliability tests, multiple linear regression analysis tests, normality tests, linearity tests, and hypothesis testing. The research was conducted at SMK Negeri 14 Jakarta, and a sample of 152 respondents was obtained using a random sampling approach. The findings of this study indicate that self-efficacy, peers, and student integrity have a partial and significant effect on academic cheating. Additionally, self-efficacy, peers, and student integrity have a simultaneous and significant effect on academic cheating. Together, self-efficacy, peers, and student integrity significantly influence academic cheating.